Is the Quantity of Government Debt a Constraint for Monetary Policy? - Mitra, Srobona (IMF Working Papers; Working Paper ;, 2007)
This paper derives an interest rate rule for monetary policy in which the interest rate response of the central bank toward an increase in expected inflation falls as debts increase beyond a certain threshold level. A debt-constrained interest rate rule and the threshold level of debt are jointly estimated for Canada during the first decade of its inflation targeting regime of the 1990s. There are three main findings of this paper. First, a high government debt could constrain monetary policy if government spending-rather than taxes-is expected to adjust in future in line with debt service costs. The 'constraint' operates through an altered policy transmission mechanism through changes in the IS curve. Second, the effects of the debt-constraint on monetary policy are quite different during booms and recessions. Third, empirical estimates show that Canadian monetary policy might have been constrained by a high government debt-GDP ratio during the 1990s. Policy was less loose than what inflation indicators called for.